(3GdJYGhf GdOhdj aj eLGd ecGaMI ZSd GdGehGd GdeJMUdI ef GdLQjeI GdefXeI hLQGFe GdeNOQGJ aj VhA GdbGfhf GdOhdj GdYGe (B/ s - (3Ydi aGQhb Ydis; (3UdGM GdOjf YGeQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3jTgO GdYGde eRjO ef MQcI QAhS GdCehGd hRhGd GdMOhO Hjf GdOhd ef NdGd GJLGg GdYGde Gdj GdYhdeI GdGbJUGOjI hJCKjQgG aj LhGfH GdMjGI GdeNJdaI(B. (3hbO GOj Zdj gPg GdXGgQI (B: (3GdKhQI GdYdejI aj YGde GdeYdheGJ hGdGJUGdGJ hSjGOI ePgH GdGbJUGO GdMQ hbGfhf GdShb(B. (3hbO GSJZdJ LeGYGJ GdLQjeI GdefXeI YHQ GdOhd gPg GdMOhO GdeaJhMI dJbje dgG THcGJ YHQ GdhWfjI eJYOOI GdaQhY aj eNJda GdOhd MjK jJe GQJcGH GdLQjeI aj GdYOjO ef GdGbGdjes
(3jTJed Ydi edGMb(B: (3UaMI (B700-876s
(3GWQhMI(B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdj, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B660-698s
Keywords: (3GdbGfhf GdOhdjs; (3GdLQjeI GdefXeIs; (3LQGFe GdeNOQGJs; (3ZSd GdCehGds; (3GdeNOQGJs; (3GdJTQjY GdeUQjs; (3GdJTQjY GdGeGQGJjs; (3GdJTQjYGJ GdhWfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs